2021
DOI: 10.1080/13573322.2021.1887846
|View full text |Cite
|
Sign up to set email alerts
|

Dispositions and coaching theories: understanding the impact of coach education on novice coaches’ learning

Abstract: Whilst coach education has been the subject of much critique, it is often the first opportunity for novice coaches to be formally taught how to coach. Nevertheless, novice coaches arrive at coach education courses with an array of pre-existing dispositions and coaching theories, referring to naturalised and self-referenced approaches towards coaching practice, which can be resistant to change. Consequently, the aim of this research was to explore the construction and development of four novice coaches' disposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Allied to personal motivations, students, even in a scenario of institutional education, negotiate the importance of learning certain contents considering the environment involved (e.g., the complexity of a sports team) (Jarvis, 2011). The student coaches in this study found in university teams an alternative for personal progress that made them more secure in their learning about coaching (De Martin-Silva et al, 2015), despite acknowledging the following: (1) university-based coach education programs in Brazil do not provide adequate preparation for students to engage in performance contexts (Milistetd et al, 2014); (2) coach education programs are limited in helping students understand their current and future coaching practice (Webb & Leeder, 2021) ; (3) despite their potential, internships still present weaknesses (Dieffenbach et al, 2011;Gomes et al, 2018;Milistetd, Ciampolini, et al, Research, Society and Development, v. 11, n. 9, e43911932001, 2022 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v11i9.32001 13 2018; Zakrajsek et al, 2015).…”
Section: Discussionmentioning
confidence: 80%
“…Allied to personal motivations, students, even in a scenario of institutional education, negotiate the importance of learning certain contents considering the environment involved (e.g., the complexity of a sports team) (Jarvis, 2011). The student coaches in this study found in university teams an alternative for personal progress that made them more secure in their learning about coaching (De Martin-Silva et al, 2015), despite acknowledging the following: (1) university-based coach education programs in Brazil do not provide adequate preparation for students to engage in performance contexts (Milistetd et al, 2014); (2) coach education programs are limited in helping students understand their current and future coaching practice (Webb & Leeder, 2021) ; (3) despite their potential, internships still present weaknesses (Dieffenbach et al, 2011;Gomes et al, 2018;Milistetd, Ciampolini, et al, Research, Society and Development, v. 11, n. 9, e43911932001, 2022 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v11i9.32001 13 2018; Zakrajsek et al, 2015).…”
Section: Discussionmentioning
confidence: 80%
“…Much of the research on sport coaching to-date has focused on how coaches learn, by either examining sources of knowledge or the life history of coaches, with eight sources of knowledge being identified within this review, namely formal education, workshops, experience, interactions with other coaches and athletes, observation, resource materials, mentoring and reflection. What is less clear, however, is an understanding of how these sources interact with contextual factors, such as the coaches' own circumstances and the learning context (e.g., Deek et al, 2013;Watts & Cushion, 2017;Stodter & Cushion, 2019;Cope et al, 2021), in what Webb and Leeder (2021) describe as a 'somewhat sobering picture' (pg. 2).…”
Section: Sources Of Coaching Knowledgementioning
confidence: 99%
“…In contrast to the studies discussed above, who conducted studies with sports coaches with previous experience, Webb and Leeder ( 2021) sought to better understand the impact of an entry level sport-specific coaching course on novice coaches' disposition and learning. Drawing on Hodkinson and colleagues' (e.g., Hager learning, and how this affects cultural and social capital as coaches develop over time (e.g., Watts & Cushion, 2017), Webb and Leeder (2021) interviewed four novice sport coaches before, during and after they completed their course. Findings suggested that coaches' dispositions and coaching theories were largely determined prior to the course beginning, but that these evolved over the course of completing the qualification and continued to change afterwards.…”
Section: Exploring the Impact Of Coach Education Over Timementioning
confidence: 99%
See 2 more Smart Citations